Vzjaimosvjaz' mezdu potrebleniem O2 i krovosnabzeniem sokrascajuscichsja mysc pri rabote raznoj moscnosti u lic, trenirujuscich aerobnuju vynoslivost' - Tchorevskij, V. I.; Litvak, A. L. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The authors assesses changes of blood flow of the calf muscles, changes in the oxygen consumption and interrelation of the oxygen consumption and muscle blood flow during various intensity to exercise of the athletes training endurance. The results of this research enlarge the knowledge and are important for the following problems in sports physiology and sport practice: